Corporate Social Responsibility and Revenue Misclassification: Evidence from India - Manish Bansal (Asian Academy of Management Journal of Accounting and Finance, 2023)
The study examines the relationship between Corporate Social responsibility (CSR) and revenue misclassification in Indian institutional settings. Malikov et al. model has been used to operationalise revenue misclassification. Using a sample of Bombay Stock Exchange listed firms spanning over 14 years (March 2009 until March 2022), I find that CSR-oriented firms prefer revenue misclassification over expense misclassification for managing core earnings, consistent with the notion that CSR firms prefer earnings management (EM) tool having a greater relative advantage in terms of reporting favourable operating performance metrics. The subsequent tests suggest that big four auditors have a constraining effect on the revenue misclassification practices of firms. The findings alert auditors about the suspected firms (high-CSR firms) that are more likely to manage earnings through revenue misclassification and suggest authorities make more mandatory disclosure requirements for recording revenue items to curb the corporate misfeasance of revenue misclassification.